Using non-spectacular radar meteor echoes to monitor lower thermosphere wind profiles - Oppenheim, Meers (2009)
We present a new method of measuring lower thermospheric wind velocity profiles by tracking non‐specular meteor echoes in time. This approach relies on having a radar following plasma irregularities as they are dragged by the neutral wind. This requires a VHF radar with interferometric capability able to point close to perpendicular to the geomagnetic field. Using a small sample of data from the Jicamarca Radio Observatory, we calculated wind speeds and directions between 90 and 110\ km with a range resolution of a few hundred meters. The measurements taken show speeds reaching 150m/s and someAmes changing by as much as 100m/s over a 6km altitude range. With some refinement of the data collection and analysis techniques, we expect that one could obtain high resolution images of lower thermospheric winds as they change in both altitude and time. We will discuss these results, the physics underlying these measurements, and the limitations.